Analisis Mutu Sie Reuboh Dalam Kemasan (Ready to Eat) Selama 7 Hari Penyimpanan - Cut Nilda; Dian Hasni; Yusriana Yusriana; Novia Mehra Erfiza (Agricultural Faculty, 2020)
Sie reuboh is a traditional cuisine from Aceh Besar district which use red meat, tallow, vinegar and some blended spices. Normally, Acehnese cooks this cuisine in with traditional clay pot. As cooking utensil, clay pot is vulnerable to breakage and has slow heat propagation compared to stainless steel pot which has long usage and good heat conductor. The use of packaging such as nylon plastic and aluminum foil in storage is also expected to affect the quality of sie reuboh. This study aims to find out sensory profile of produced sie reuboh by using ten attributes (colour/brightness, aroma (sour, spicy, meaty), flavor (hot spicy, sour, salty, umami) and texture (tenderness, chewiness). Sie reuboh was cooked in two types of cooking ware (earth clay pot and stainless steel pot) and then store in nylon and aluminum foil packaging for 7 days. The obtained data is statistical analyzed with ANOVA and DMRT. The results showed that attribute sour aroma, hot spicy flavor, umami and tenderness of sie reuboh cooked with stainless steel has higher notes, whereas other attributes showed no significant effect. Type of packaging also showed no significant effect for these ten attributes except sour aroma. As conclusion, it can be stated that stainless steel provides sie reuboh with better sensory properties compare to clay pot.